2019
DOI: 10.1002/iid3.272
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of uncontrolled allergic rhinitis in a hospital setting of Kinshasa, Democratic Republic of Congo

Abstract: AimTo determine the clinical and allergic features of uncontrolled allergic rhinitis (UCAR) in the Democratic Republic of Congo (DRC).MethodsObservational cross‐sectional study of 311 patients with UCAR. Allergic rhinitis was diagnosed clinically with sensitization to inhalant allergens and then confirmed by skin prick test. Severity was assessed using the Visual Analog Scale (VAS), with VAS scores greater than or equal to 5 used as cut off to determine uncontrolled status.ResultsThe mean age of UCAR patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Patients with a score ≥5 on this scale are considered to have uncontrolled AR (UCAR) ( 4 , 5 ). Several studies have reported an increase in UCAR frequency in some countries such as France (71.7%) ( 6 ), Italy (>60%) ( 7 ), Tunisia (62%) ( 8 ), and the Democratic Republic of Congo (DRC) (75.5%) ( 9 ). On average, one-fifth of patients with AR have bothersome symptoms of AR despite adequate medical treatment abiding to the Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a score ≥5 on this scale are considered to have uncontrolled AR (UCAR) ( 4 , 5 ). Several studies have reported an increase in UCAR frequency in some countries such as France (71.7%) ( 6 ), Italy (>60%) ( 7 ), Tunisia (62%) ( 8 ), and the Democratic Republic of Congo (DRC) (75.5%) ( 9 ). On average, one-fifth of patients with AR have bothersome symptoms of AR despite adequate medical treatment abiding to the Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines ( 10 ).…”
Section: Introductionmentioning
confidence: 99%